Secondary Stroke Prevention in People With Schizophrenia - Moira K. Kapral; Joan Porter; Paul Kurdyak; Amy Y. X. Yu; Emilie Matheson; Jiming Fang; Leanne K. Casaubon; Eshita Kapoor; Kathleen A. Sheehan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background People with schizophrenia are less likely than those without to be treated for cardiovascular disease. We aimed to evaluate the association between schizophrenia and secondary preventive care after ischemic stroke. Methods and Results In this retrospective cohort study, we used linked population‐based administrative data to identify adults who survived 1 year after ischemic stroke hospitalization in Ontario, Canada between 2004 and 2017. Outcomes were screening, treatment, and control of risk factors, and receipt of outpatient physician services. We used modified Poisson regression to model the relative risk of each outcome among people with and without schizophrenia, adjusting for age and other factors. Among 81 163 people with ischemic stroke, 844 (1.04%) had schizophrenia. Schizophrenia was associated with lower rates of screening for hyperlipidemia (60.5% versus 66.0%, adjusted relative risk [aRR] 0.88 [95% CI, 0.84–0.93]) and diabetes (69.4% versus 73.9%, aRR 0.93 [95% CI, 0.89–0.97]), prescription of antihypertensive medications (91.2% versus 94.7%, aRR 0.96 [95% CI, 0.93–0.99]), achievement of target lipid levels (low‐density lipoprotein <2 mmol/L) (30.6% versus 34.6%, aRR 0.86 [95% CI, 0.78–0.96]), and outpatient specialist visits (55.3% versus 67.8%, aRR 0.78 [95% CI, 0.74–0.83]) or primary care physician visits (94.5% versus 98.5%; aRR 0.96 [95% CI, 0.95–0.98]) within 1 year. There were no differences in prescription of antilipemic, antiglycemic, or anticoagulant medications, or in achievement of target hemoglobin A1c ≤7%. Conclusions People with stroke and schizophrenia are less likely than those without to receive secondary preventive care. This may inform interventions to improve poststroke care and outcomes in those with schizophrenia.